2000
DOI: 10.1051/lait:2000150
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of monoterpenes and sesquiterpenes from forages into milk fat

Abstract: The transfer of monoterpenes and sesquiterpenes from forages into milk fat was studied in a group of cows fed successively with forages containing high and low amounts of these substances. In a first 24-d period the cows received 11 kg of a cocksfoot hay containing low quantities of monoterpenes and sesquiterpenes. In a second 36-d period, 3 kg of the cocksfoot were replaced by 3 kg of yarrow, a plant rich in terpenoids. In a third 24-d period the cows returned to the cocksfootbased diet they were fed in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
3
13

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 14 publications
9
119
3
13
Order By: Relevance
“…Secretion in milk could be considered as a route of terpene elimination. Observations in this study agree with the results obtained by Viallon et al (2000), who observed that monoterpene content in milk increased more rapidly than sesquiterpene content after a terpene-rich diet.…”
Section: --supporting
confidence: 93%
“…Secretion in milk could be considered as a route of terpene elimination. Observations in this study agree with the results obtained by Viallon et al (2000), who observed that monoterpene content in milk increased more rapidly than sesquiterpene content after a terpene-rich diet.…”
Section: --supporting
confidence: 93%
“…Owing to the strong odoriferous properties of EOs, their transfer could alter the organoleptic quality of animal products (Viallon et al, 2000;Ando et al, 2001;Burt, 2004). Their observed beneficial and harmful effects are in fact associated.…”
Section: Jouany and Morgavimentioning
confidence: 99%
“…They abound in certain species, dicotyledons in particular [26,74]. These molecules very rapidly pass into the milk [124] and are found in cheese in a much greater quantity when the animals are fed dicotyledon-rich natural grass forage than when they are fed concentratebased rations [85], or monospecific forage [13,15,17,123]. However, if these molecules may be effective markers of cheeses' origins [14,26,45], it appears that changes in their concentration in cheese do not suffice to exert any marked direct effect on cheese flavour [17,85,119].…”
Section: Direct Transfermentioning
confidence: 99%